Creole Jews : Negotiating Community in Colonial Suriname. - Vink, Wieke (Caribbean Series., 2010)
This study presents a refined analysis of Surinames-Jewish identifications. The story of the Surinamese Jews is one of a colonial Jewish community that became ever more interwoven with the local environment of Suriname.